Balancing water conservation and health: do water-saving showerheads impact the microbes we breathe in during showering? - Pitell, Sarah; Woo, Cheolwoon; Trump, Evan; Haig, Sarah-Jane (Frontiers in Microbiomes, 2024)
Low-flow showerheads offer consumers economic and water-saving benefits, yet their use may inadvertently affect the microbial content of produced water and water-associated aerosols. This study aimed to compare the abundance and microbial composition of bacteria in shower water and associated respirable aerosols produced by various low flow rate (1, 1.5, and 1.8 gpm) showerheads. Our findings indicate that the lowest-flow showerhead produces water with lower total microbial and opportunistic bacterial pathogen densities compared to higher low flow rate counterparts. However, microbiome analysis revealed that 1.8 gpm flow rate showerheads exhibit reduced abundance of Gram-negative organisms and common biofilm-forming organisms, suggesting potentially lower pathogenicity compared to 1 and 1.5 gpm low-flow showerheads. Additionally, the number of respirable aerosols produced by showerheads as well as the partitioning of certain microorganisms from the water to aerosol phases was negatively correlated with flow rate, suggesting that there may be increasing exposure potential to pathogenic bioaerosols when using a 1gpm showerhead compared to a 1.8 gpm showerhead. However, the 1.5 gpm showerhead seemed to balance microbial partitioning, aerosol generation, and water conservation. Moreover, the microbial composition of aerosols produced from shower water was more influenced by the age of the showerhead than the flow rate, highlighting the significance of biofilm formation on the microbial community. Overall, our findings underscore the importance of evaluating the microbial risk associated with low-flow showerheads using multiple metrics in both water and aerosols, and dynamically assessing this over time, to ensure accurate future risk assessment.